2017
DOI: 10.1176/appi.ps.201600114
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Decision Making and Mental Health Service Use Among Persons With Severe Mental Illness Across Europe

Abstract: A preference for shared decision making may reduce health care costs by reducing inpatient admissions. Patient satisfaction with decisions was a predictor of costs, and clinicians should maximize patient satisfaction with CDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 15 publications
0
14
0
3
Order By: Relevance
“…the diagnosis of illness) (De las Cuevas & Peñate, ; De las Cuevas, Peñate, et al, ; Park et al, ). In studies reporting SDM as a single dimensional concept, most consumers preferred SDM, and a minority of them preferred passive involvement (Cosh et al, ; De las Cuevas & Peñate, ; De las Cuevas, Peñate, et al, ; Ehrlich & Dannapfel, ; Liebherz et al, ; Nott, Mcintosh, Taube, & Taylor, ). Specifically, three articles reported that consumers also preferred shared involvement in physical health (Ehrlich & Dannapfel, ; Small et al, ; Wright‐Berryman & Kim, ; Wright‐Berryman & Cremering ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…the diagnosis of illness) (De las Cuevas & Peñate, ; De las Cuevas, Peñate, et al, ; Park et al, ). In studies reporting SDM as a single dimensional concept, most consumers preferred SDM, and a minority of them preferred passive involvement (Cosh et al, ; De las Cuevas & Peñate, ; De las Cuevas, Peñate, et al, ; Ehrlich & Dannapfel, ; Liebherz et al, ; Nott, Mcintosh, Taube, & Taylor, ). Specifically, three articles reported that consumers also preferred shared involvement in physical health (Ehrlich & Dannapfel, ; Small et al, ; Wright‐Berryman & Kim, ; Wright‐Berryman & Cremering ).…”
Section: Resultsmentioning
confidence: 99%
“…Mental health professionals across various professions and settings were unanimously favourable towards SDM (Ali, Smith, Mican, & Brown, ; Chong et al, , ; Cosh et al, ; De las Cuevas, Rivero‐Santana, Perestelo‐Pérez, Pérez‐Ramos, & Serrano‐Aguilar, ; Fisher, Manicavasagar, Sharpe, Laidsaar‐Powell, & Juraskova, ; Lukens, Solomon, & Sorenson, ; Shepherd, Shorthouse, & Gask, ; Younas, Eleanor, Nikki, Dolly, & Maidment, ). Some MHPs particularly stressed that SDM should be flexible and determined by them, as the consumers’ insight might fluctuate (Chong et al, ; Shepherd et al, ; Younas et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations